The metabolic signaling of the nucleoredoxin-like 2 gene supports brain function - Céline Jaillard (Elsevier, 2021)
The nucleoredoxin gene NXNL2 encodes for two products through alternative splicing, rod-derived cone viability factor-2 (RdCVF2) that mediates neuronal survival and the thioredoxin-related protein (RdCVF2L), an enzyme that regulates the phosphorylation of TAU. To investigate the link between NXNL2 and tauopathies, we studied the Nxnl2 knockout mouse (Nxnl2−/−). We established the expression pattern of the Nxnl2 gene in the brain using a Nxnl2 reporter mouse line, and characterized the behavior of the Nxnl2−/− mouse at 2 months of age. Additionally, long term potential recording and metabolomic from hippocampal specimens were collected at 2 months of age. We studied TAU oligomerization, phosphorylation and aggregation in Nxnl2−/− brain at 18 months of age. Finally, newborn Nxnl2−/− mice were treated with adeno-associated viral vectors encoding for RdCVF2, RdCVF2L or both and measured the effect of this therapy on long-term potential, glucose metabolism and late-onset tauopathy. Nxnl2−/− mice at 2 months of age showed severe behavioral deficiency in fear, pain sensitivity, coordination, learning and memory. The Nxnl2−/− also showed deficits in long-term potentiation, demonstrating that the Nxnl2 gene is involved in regulating brain functions. Dual delivery of RdCVF2 and RdCVF2L in newborn Nxnl2−/− mice fully correct long-term potentiation through their synergistic action. The expression pattern of the Nxnl2 gene in the brain shows a predominant expression in circumventricular organs, such as the area postrema. Glucose metabolism of the hippocampus of Nxnl2−/− mice at 2 months of age was reduced, and was not corrected by gene therapy. At 18-month-old Nxnl2−/− mice showed brain stigmas of tauopathy, such as oligomerization, phosphorylation and aggregation of TAU. This late-onset tauopathy can be prevented, albeit with modest efficacy, by recombinant AAVs administrated to newborn mice. The Nxnl2−/− mice have memory dysfunction at 2-months that resembles mild-cognitive impairment and at 18-months exhibit tauopathy, resembling to the progression of Alzheimer's disease. We propose the Nxnl2−/− mouse is a model to study multistage aged related neurodegenerative diseases. The NXNL2 metabolic and redox signaling is a new area of therapeutic research in neurodegenerative diseases.